Psikoedukasi Menurunkan Beban Keluarga yang Mengalami Stigma sebagai Klien Tuberkulosis dan Riwayat Putus Obat - Endar Cahyawati; Achir Yani S. Hamid; Yossie Susanti Eka Putri; Herni Susanti; Ria Utami Panjaitan (Journal of Telenursing (JOTING), 2023)
This study aims to analyze the implementation of family psychoeducation in reducing the burden on families who experience stigma as tuberculosis clients and have a history of drug withdrawal. The research method used was a case report on one family with one caregiver who experienced the burden and anxiety of tuberculosis clients with a history of drug withdrawal. Interviews and observations used the Hamilton Rating Scale (HARS) instrument on caregivers and the Zarit Burden Interview (ZBI) instrument. The results showed that family psychoeducation with six sessions at four meetings could reduce anxiety and burden on caregivers with an initial HARS score of 29 to 16 (mild anxiety) and a ZBI score of 44 to 34 (light-moderate perceived burden). In conclusion, family psychoeducation affects client adherence to treatment; in family psychoeducational interventions, health workers coordinate with caregivers to reduce anxiety and increase caregiver knowledge about the client's illness. Family psychoeducation also plays a role in overcoming social and self-stigma in clients and families. Keywords: Family Psychoeducation, Drug Dropout, Stigma, Pulmonary Tuberculosis